2017
DOI: 10.1111/cpf.12476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistance training set volume on upper body muscle hypertrophy: are more sets really better than less?

Abstract: The analysis suggests that, statistically, high set volumes (≥3) are not significantly better than low set volumes (<3) in regard to UBMH in untrained subjects. For trained subjects, the literature is lacking in well-designed studies comparing low and high training volumes, as well as analysing upper and lower body muscles separately. Therefore, it is not possible to conclude that high volume of sets offers better results than low volume of sets for UBMH, and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…A recent meta-analysis by Schoenfeld et al ( 14 ) demonstrated significantly greater hypertrophic responses after completion of 10 sets per week of a resistance exercise emphasizing specific musculature compared to <5 sets per week. However, others have suggested that a plateau in the hypertrophic response exists beyond select RT doses ( 33 ). Our data indicate no clear plateau in RT-induced muscle mass increases when RT volumes are increased from 10 sets of 10 repetitions at 60% 1RM per exercise per week up to 32 sets per week, and this interpretation stems from the significant increases observed in DXA LBM from weeks 1 to 3 and 3 to 6.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis by Schoenfeld et al ( 14 ) demonstrated significantly greater hypertrophic responses after completion of 10 sets per week of a resistance exercise emphasizing specific musculature compared to <5 sets per week. However, others have suggested that a plateau in the hypertrophic response exists beyond select RT doses ( 33 ). Our data indicate no clear plateau in RT-induced muscle mass increases when RT volumes are increased from 10 sets of 10 repetitions at 60% 1RM per exercise per week up to 32 sets per week, and this interpretation stems from the significant increases observed in DXA LBM from weeks 1 to 3 and 3 to 6.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the effect of increasing from 1 set to 2-3 sets was greater than increasing from 2-3 to 4-6 sets. La Scala et al also found that performing a relatively low number of sets (< 3) twice per week significantly increased upper-body muscle mass, and that performing additional sets only provided small incremental benefits [24]. However, the optimal number of sets is still a controversial topic, and some authors advocate the necessity of high volume (> 10 weekly sets) to optimize the hypertrophic response [15].…”
Section: Training Frequency and Volumementioning
confidence: 99%
“…A specific upper threshold for volume has not been determined and undoubtedly would vary between individuals based on a multitude of genetic and lifestyle factors. Hypothetically, the upper threshold could also vary between different muscle groups (117).…”
Section: Evidence From the Literaturementioning
confidence: 99%